Caracterização metabólica e cinética do cultivo de três hibridomas para produção de imunoglobulinas com especificidade e antígenos eritrocitários para uso hemoterápico - Ferreira, Douglas (Universidade Federal de São Carlos, 2007)
In the last two decades mammalian cell cultures have been broadly used for the industrial production of pharmaceutical, proteins, in particular the monoclonal antibodies by cultures of murine hybrid cells (hybridoma). The development of bioprocess for industrial scale of monoclonal antibodys (MAbs) depends on the determination and optimization of several physiological and metabolic parameters. In this work are shown preliminary development results of the bioprocess for production of three MAbs for blood typing through the ABO system, with is of great interest for Brazilian public health. Experiments with three lineages of murine hybridomas which were able to secret three different immunoglobulins with specificity to ABO human blood antigens were accomplished in Spinner flasks using RPMI 1640 medium and fetal bovine serum (FBS) in concentrations of 20 and 10 % vv, temperature of 37 ºC and pH 6.8 7.4 .The three hybridomas showed very different growth patterns in these culture medium The cultivation with 20 % v/v of FBS as much as the cultivation with cells adapted to 10 % v/v FBS showed the necessity of a better balance of the amino acids formulation in the culture medium in order to improve the specific maximum grow rate (µmáx) and maximum cells density (CXmáx).
Keywords: Hibridomas; Células cultivadas; Célula animal; Soro fetal bovino; ENGENHARIAS::ENGENHARIA QUIMICA